2019
DOI: 10.15713/ins.jcri.273
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the surgical management of odontogenic keratocyst

Abstract: Odontogenic keratocyst (O) is the second most common odontogenic cyst in the oral cavity accounting for 10% of all cysts. Controversies regarding its tumor-like behavior, recurrences, and management have been the reason for this cyst to be exclusive unlike any other odontogenic cyst. In recent literature, the once named keratocystic odontogenic tumor has again been renamed as OKC, thus establishing it as a cyst with an aggressive behavior. In this article, we describe the conservative and radical treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Thus, ultimately the type of management depends on the site, size, extent of the lesion, perforation of overlying mucosa, and age of the patient. [ 24 ] Molecular factors such as the synthesis of interleukin-1 and interleukin-6 by keratinocytes,[ 25 ] increased expression of parathyroid hormone-related protein, and the greater frequency of proliferating cell nuclear antigen (PCNA), Ki-67, p53, Bcl-1, and Gp-38 positivity are also quoted. Few studies have found p16, p53, PTCH, MCC, TSLC 1, LTAS2, and FHT genes, exhibiting allelic losses in heterozygosity as causes of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ultimately the type of management depends on the site, size, extent of the lesion, perforation of overlying mucosa, and age of the patient. [ 24 ] Molecular factors such as the synthesis of interleukin-1 and interleukin-6 by keratinocytes,[ 25 ] increased expression of parathyroid hormone-related protein, and the greater frequency of proliferating cell nuclear antigen (PCNA), Ki-67, p53, Bcl-1, and Gp-38 positivity are also quoted. Few studies have found p16, p53, PTCH, MCC, TSLC 1, LTAS2, and FHT genes, exhibiting allelic losses in heterozygosity as causes of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Tradicionalmente, se indicaba solo en pacientes con lesiones quísticas maxilares pequeñas, identificables en endoscopia, localizadas en relación al complejo osteomeatal o a la pared maxilar medial o al estar asociadas a piezas dentarias pequeñas 22,[26][27][28] . Sin embargo, las características, anteriomente mencionadas, no constituyen criterios de selección estrictos; existendo reportes de casos manejados de forma endoscópica exclusiva, independiente del tamaño de la lesión, de su histología o de su localización en el hueso maxilar, siendo utilizada inclusive en casos de lesiones en relación con el piso de órbita o nervio infraorbitario 1,[27][28][29] .…”
Section: Manejo Endoscópicounclassified
“…[12] OKC have been differentiated from Ameloblastomas, Dentigerous Cysts, Radicular Cysts, Simple Bone Cysts, and Central Giant Cell Granulomas. [8] It is found that a distinctive epithelial cell proliferation in KCOT may determine its unique growth and behavior pattern. The growth pattern of KCOT epithelium is characterized by heterogeneity, and explains the infiltrative growth in OKCs in contrast to the expansive growth in other cysts.…”
mentioning
confidence: 99%
“…[11] The superficial luminal surface of the epithelium demonstrates corrugated parakeratinized epithelium. [11,8] The palisaded basal layer are hyperchromatic columnar to cuboidal cells and are described as having "picket fence" or "tomb-stone" appearance with keratinaceous material in the cystic cavity. [11,8] Epithelial islands, daughter cysts, hyaline bodies, epithelial budding of the basal layer, with dystrophic calcification have also been reported in OKC.…”
mentioning
confidence: 99%
See 1 more Smart Citation